Ts. Dr. Mohd Riduwan produced an automatic cupping machine to replace existing phlegm suction machine - Nur Hartini, Mohd Hatta (UMPSA, 2023)
PEKAN, 18 August 2023 – Cupping therapy is a form of alternative medicine that is widely practiced by Muslim, Chinese and European communities.